Development and initial validation of the Partnership Scale-DanceSport Couples - Liu, Xiuxia; Yang, Guan; Wang, Shen; Wang, Xiangfei; Wang, Xuelian (Frontiers in Psychology, 2023)
Introduction DanceSport is described as a dance involving a male–female partner. It is important to comprehend the partnership between dance couples so that their competitive performance can be effectively supported. However, only a few studies have verified the influence of partnership between DanceSport couples on competitive performance and explored its psychological mechanism to provide means to deal with the partnership. The reason was that there was a lack of appropriate assessment tools. Aims This multi-study outlines the development, content, and construct validity of a novel, mixed-method tool to assess DanceSport partnership. Methods The development of the Partnership Scale-DanceSport Couples (PS-DSC) included four studies and data from four samples of Chinese elite dancers (N = 914 total). In stage 1, outlined in study 1, PS-DSC items were generated and then refined using the feedback provided by academics, sports coaches, and elite dancers. In stage 2, outlined in studies 2 and 3, exploratory factor analysis and confirmatory factor analysis were used to examine the structure of the PS-DSC items. In stage 3, outlined in study 4, composite reliability, discriminant validity, and convergent validity were assessed. The result of this process was a 13-item three-factor instrument. Based on these initial findings, the PS-DSC provided the first valid and reliable way of measuring partnerships between DanceSport couples. Conclusion This study has taken the promising first step in developing a tool to comprehensively measure partnerships between DanceSport couples.